“I am all of them”. Gloria Trevi: gender and patriarchy before the Me Too movemen - Núñez Moya, Jáirol (2021)
This article is an approach to the work of Colombian writer Álvaro Mutis. Through some of his works (lyric and narrative) it is sought to observe the correspondence of writing and rewriting of the literary journey. The objective is to study the double journey in Mutis' work. A first record of the journey is found in the writing of the poems, and a second, in the rewriting of his novels. This relationship of correspondence or intertextuality is appreciated and read in the works: Primeros poemas (1947-1952) and La Nieve del Almirante (1986). However, river and land travel are present in all Mutis literature through his character Maqroll el Gaviero.